North Atlantic Regional Water Resources Study. Annex 2. - CORPS OF ENGINEERS NEW YORK NORTH ATLANTIC DIV (1972)
Fourteen State Programs are presented in this Annex and each is a reformulation along state boundaries of the appropriate Area Programs of Annex 1. The procedures used for these reformulations were agreed to by the personnel of the agencies responsible for the appendices to the NAR Report. These are mixed objective State Programs and the reformulations were done in a manner that would insure no changes in the plan formulation decisions on alternative planning elements: objectives, needs, devices, benefits and costs. (Author) Annex 2 to report dated Jun 72, AD-A036 616. See also Appendix A, AD-A036 619.